Moments of liberty. (Self-)censorship Games in the Essays of Virginia Woolf - Pająk, Paulina (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2018)
What is surprising in Virginia Woolf’s essays is the scale and the audacity of her intellectual searches – in the time of increased repressive censorship and growing totalitarianisms, she approached the themes of freedom which have remained controversial ever since. The article presents the essayistic nature as a strategy applied by Woolf in her personal essays to avoid censorship, and intentionally expand the limits of freedoms important to her. The author offers an outline of the mechanism of repressive censorship and the chilling effect it worked in the interwar United Kingdom based on the examples of suspensions of outstanding modernist works and show-trials of writers. She presents three areas of study of freedom in Woolf’s essays: women’s emancipation, tolerance towards non-heteronormative persons, and pacifism, as well as the areas of private and public (self-)censorship which existed therein.